Structural characteristics and application of Cu oblique nano-rod thin films for surface-enhanced Raman spectroscopy (SERS) - Babaei, Reza; Savaloni, Hadi (Applied physics. A, Materials science & processing, 2021)
In this work, oblique angle deposition technique is used to fabricate Cu nano-rods with different growth angles on two types of substrates (Cu and (Ti sputtered)/Si). Field emission electron microscope and atomic force microscope as well as X-ray diffraction were used to characterize the structure, morphology and crystallography of the produced samples. Raman spectroscopy of Cu nano-rods on both type of substrates impregnated with 4, 4’ Bipyridine (Bipy) molecules was carried out by means of 532 nm wavelength laser. Results showed that by increasing the deposition angle the grain size, surface roughness and porosity increase in consistent with published theoretical, simulation and experimental results. Highest enhancement factor for SERS obtained for nano-rods deposited at lowest deposition angle of 30º owing to smaller grain sizes (sharp-tips/(hot spots)) which leads to increased electric field at these sites which in turn enhances the Raman peak. In addition, at this deposition angle the shadowing is less effective and higher number density of nano-rods and more uniform distribution of the nano-rods is achieved. Hence, situation for higher enhancement of Raman peak is obtained. Comparison of the Surface-enhanced Raman spectroscopy (SERS) results for Bipy obtained in this work with the published literature using Ag and Au substrates (two mostly used elements for SERS) in different shapes showed that Cu nano-rods of this work produced significantly higher enhancement factor.